2004
DOI: 10.1111/j.1540-8159.2004.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Catheter Ablation for Arrhythmic Storm in Patients with An Implantable Cardioverter Defibrillator

Abstract: The aim of the study was to analyze the usefulness of RFA in controlling arrhythmic storm due to hemodynamically stable VT in a cohort of patients with an ICD and to evaluate the incidence of arrhythmic storm among patients with an ICD. A group of 13 (3%) of 403 consecutive ICD recipients were submitted to RFA of VT during an arrhythmic storm. Two additional patients were referred from other institutions. Standard criteria were used for VT endocardial ablation. A transcatheter epicardial approach was required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 30 publications
1
18
0
2
Order By: Relevance
“…Sra 21 Two further cohort studies of catheter ablation for ES also showed high acute success rate and significant survival benefit. 22,23 In agreement with these data, we found that ES ablation has an acute and long-term success of 92%. Moreover, despite the fact that mortality of ES patients is increased; there is a tendency of reduced mortality when ablated patients are compared to a conservative therapy.…”
Section: The Impact Of Catheter Ablationsupporting
confidence: 87%
“…Sra 21 Two further cohort studies of catheter ablation for ES also showed high acute success rate and significant survival benefit. 22,23 In agreement with these data, we found that ES ablation has an acute and long-term success of 92%. Moreover, despite the fact that mortality of ES patients is increased; there is a tendency of reduced mortality when ablated patients are compared to a conservative therapy.…”
Section: The Impact Of Catheter Ablationsupporting
confidence: 87%
“…Additionally, oral quinidine therapy can be used if arrhythmia is persistent [76]. In the rare case of failure of these therapeutic options, radiofrequency-catheter ablation of the ventricular ectopic foci can be attempted, but should be regarded as a highly specialized modality [77,78]. Though exceedingly rare, patients with BrS suffering from recurrent arrhythmic storm, refractory to all other treatment, should be considered candidates for cardiac transplantation.…”
Section: Arrhythmic Storm and Inappropriate Implantable Cardioverter mentioning
confidence: 97%
“…Additionally, oral quinidine therapy can be started if arrhythmic storms cannot be controlled [73]. In case of failure of these therapeutic options, radiofrequency-catheter ablation of the triggering ventricular ectopies can be attempted, but should be regarded as a highly specialized 'ultimate stage' treatment [74,75]. In very rare cases, BrS patients suffering from recurrent arrhythmic storms, refractory to any other treatment, should be considered candidates for cardiac transplantation.…”
Section: Arrhythmic Storm In the Brugada Syndromementioning
confidence: 98%